Classe de distribuições série de potências inflacionadas com aplicações - Silva, Deise Deolindo (Universidade Federal de São Carlos, 2009)
This work has as central theme the Inflated Modified Power Series Distributions, where the objective is to study its main properties and the applicability in the bayesian context. This class of models includes the generalized Poisson, binomial and negative binomial distributions. These probability distributions are very helpful to models discrete data with inflated values. As particular case the - zero inflated Poisson models (ZIP) is studied, where the main purpose was to verify the effectiveness of it when compared to the Poisson distribution. The same methodology was considered for the negative binomial inflated distribution, but comparing it with the Poisson, negative binomial and ZIP distributions. The Bayes factor and full bayesian significance test were considered for selecting models.
Keywords: Estatística matemática; Distribuição (Probabilidades); Séries de potências; Distribuição de Poisson; Distribuição binomial negativa; Inflated modified power series distributions; Zero inflated poisson models; Zero inflated negative binomial models; Selection of models; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA